The determination of normal stresses in cross-section of the four-flue reinforced concrete chimney - Borzęcki, Krzysztof; Słowik, Marta (Budownictwo i Architektura / Civil and Architectural Engineering, 2008)
In the paper the way of calculation of compressive stresses in the cross-section of a four-flue reinforced concrete chimney has been presented. Two types of cross section have been considered: the full cross section and the cross section weakened by openings. The analysis described in the paper refers to the chimney arrangement in diamond shape in relation to wind flow.